The integration of sunnah fasting contributes to the character development of students - Muhammad Fadhil Husein; Muhajir Muhajir (Himpunan Pengembang Kurikulum Indonesia, 2026)
Fasting is a form of worship that has value and can be integrated into character education. This study examines the implementation and impact of the Monday-Thursday sunnah fasting program on the development of students' spiritual character at MA PSA Istiqomah Islamiyah Pondok Modern Al-Furqon. This study used a descriptive qualitative approach, relying on participant observation, in-depth interviews with school officials and students, and document analysis to collect data. The results indicate that the program was implemented effectively and well-planned. Participation in the program significantly promoted positive character traits such as discipline, patience, and the ability to manage emotions, as well as strengthening sincerity and social awareness. There was an increase in spiritual awareness and a decrease in inappropriate verbal behavior. Several challenges, such as limited supervision outside of school and students' physical conditions, were addressed through schedule adjustments and health support. Continuous teacher evaluation and communication with families contributed to the program's success. Overall, the Monday-Thursday sunnah fasting program has proven to play a significant role in creating a religious atmosphere in schools, increasing spiritual intelligence, and serving as a strategic model for Islamic character education. Abstrak Puasa adalah salah satu ibadah yang memiliki nilai dan dapat diintegrasikan ke dalam pendidikan karakter. Penelitian ini mengulas pelaksanaan dan dampak program puasa sunah Senin-Kamis terhadap pengembangan karakter spiritual murid di MA PSA Istiqomah Islamiyah Pondok Modern Al-Furqon. Penelitian ini menggunakan pendekatan kualitatif deskriptif, dengan mengandalkan observasi partisipatif, wawancara mendalam dengan pihak sekolah dan murid, serta analisis dokumen untuk mengumpulkan data. Hasil menunjukkan bahwa program ini terlaksana secara efektif dan terencana dengan baik. Partisipasi dalam program ini secara signifikan mempromosikan karakter positif seperti disiplin, kesabaran, dan kemampuan mengelola emosi, serta memperkuat keikhlasan dan kepedulian sosial. Terdapat peningkatan kesadaran spiritual dan penurunan perilaku verbal yang kurang pantas. Beberapa tantangan, seperti minimnya pengawasan di luar sekolah dan kondisi fisik murid, dapat diatasi melalui penyesuaian jadwal dan dukungan kesehatan. Evaluasi berkelanjutan oleh guru dan komunikasi dengan keluarga turut mendukung keberhasilan program. Secara keseluruhan, program puasa sunah Senin-Kamis terbukti berperan penting dalam menciptakan suasana religius di sekolah, meningkatkan kecerdasan spiritual, serta menjadi model strategis bagi pendidikan karakter Islami. Kata Kunci: karakter murid; pendidikan karakter; pendidikan spiritual; puasa sunah